Edukasi Pemasaran Digital dan Perhitungan Harga Pokok Penjualan di Desa Lambangsari, Kecamatan Tambun Selatan, Kabupaten Bekasi - Adil Akbar Muhammad; Affif Andra Saputro; Andi Zahira Al Humairoh; Dewi Sani Sukma; Risda Rizkillah; Aqilla Fadia Wahono; Daffa Rafiandra Haryono; Indira Ariesta; Muhammad Hamzah Aditama (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The fast development of the world affects changes in various sectors, one of which is business. The situation is becoming increasingly difficult with the Covid-19 pandemic situation which limits the mobility of business actors in doing business. Based on this background, the Bekasi Kab 02 KKN-T group carried out digital marketing and HPP education activities aimed at providing solutions to overcome marketing issues during the pandemic and making MSMEs able to compete well in this era. This program was implemented 3 times with a combination of online and offline activities on July 2021. The total participants involved in this activity were 15 people. We carry out digital marketing and HPP education with a hybrid discussion method with online socialization and education as well as practices that are carried out directly at MSME locations. The results showed that based on the pre and post tests conducted by eight participants, there was an increase in the number of participants who answered correctly on four of the six questions and even all participants answered correctly on two questions. A total of 6 from 8 participants got an increased score from before the presentation of the material. While the other 2 from 8 participants did not show any change in score. This result shows that the activity can increases the knowledge of MSME actors in using Instagram to make online sales and increases understanding of the calculation of basic commodities.